Contextual influences on financial preparedness of middle-aged workers: A four-country comparative life course study. Issue 4 (2nd October 2019) - Kasper, Hans; Mathur, Anil; Ong, Fon Sim; Shannon, Randall; Yingwattanakul, Preecha
ABSTRACT: In countries where pensions are not the main responsibility of employers or governments, workers need to plan for their own postretirement financial well-being. This study investigates the financial preparedness of middle-aged workers in the United States, the Netherlands, Thailand, and Malaysia. Within- and between-country differences of three variables – financial satisfaction, financial knowledge, and saving proneness – are examined as indicators of financial preparation and financial well-being. The life course paradigm provides the basis for the conceptual framework. In addition to structural factors unique to each of the four countries, the study considers the effects of contextual variables, including individual attributes, early-in-life socialization experiences, and variables that locate the person in social structures. The results of this exploratory study show how the impact of these variables on the three indicators of financial preparedness of middle-aged workers differs across the four countries. Socioeconomic status is the only variable that positively affects financial satisfaction in all four countries. The results also shed light on the value of the life course approach for understanding individual- and country-based differences in the levels of preparation for financial well-being in later life.